DELIBERATIVE DEMOCRACY AND GENDER EQUALITY: A CASE STUDY OF THE 2023 WOMEN'S FOOTBALL WORLD CUP IN SOCIAL AUDITING AND CITIZEN TRANSPARENCY - Özdemir, Marina; Bettine, Marco (ARACÊ, 2024)
The article seeks to analyze deliberative democracy, based on Jürgen Habermas' theory, applying it in the context of public and private entities, with a focus on gender equality in the 2023 Women's Football Cup. The article will present a replicable model of social auditing, integrating Habermas' communicative rationality with the guidelines of the Brazilian Audit Courts. A connection will also be established between communicative rationality and administrative practices for the management of complex systems, since they share foundations of validity, correctness, sincerity and veracity. The questions are based on the reports produced by the international media during the mega-event, using gender inequality as a category. The central argument lies in measuring the permeability of democratic civic common sense and identifying barriers to communication and effective engagement. The article seeks to contribute to the formation of citizenship and integration between theory and practice in the face of the challenges of participatory democracy. The research presents two important results, the first confirms recent research on gender inequality in sport, as the media framework showed disparities in women's football, and the second is the non-compliance with the rules of citizen transparency of sports entities.